THE ANALYSIS OF DEATH THEME IN “THE FAULT IN OUR STAR” STORY BY JOHN GREEN - Syielvi Dwi Febrianty; Tomi Arianto; Nitasri Murawaty Girsang; Mirda Aryadi (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This research aimed to reveal the phenomenon of death in literary work. The theme of death is sometimes ignored by literary critics because it is often seen as a spice in the story. In fact, the narrative of death has a very significant that determines the plot in the story. Ross (2009) a French psychologist put forward the theoretical concept of this phenomenon with the theory of death and dying. Psychologically, there are several stages that are experienced by people who are facing terminal illness or people who are left behind in the face of death. Departing from several conceptual deaths, the researchers determined the research data source in the form of a story by John Green entitled